Biomass and root stem production of a colony-forming willow (Salix interior) on highly disturbed, low fertility sites. (March 2015) - Mosseler, Alex; Major, John E.
Abstract: This study describes biomass production, colony formation, and clonal spread via root stems (RS) of a wide-ranging North American willow species, Salix interior Rowlee (INT), one of the few willows that spread via vegetatively reproduced colonies, which can result in hundreds of upright stems arising from a shallow horizontal root network. Eight INT clones were tested in a common-garden experiment on two distinct site types (shale rock overburden and coarse gravel erosion sediments) with very low nitrogen and nutrients on a former coal mine site. Survival, height growth, aboveground biomass, and number of root stems (NRS) were quantified following 3 years of growth after establishment as rootless stem cuttings. Clonal differences were significant for survival and height at age 3. Survival was significantly greater on the coarse gravel outwash than shale rock overburden after the first and third year, but differences were only significant in the first year. There was a significant positive relationship between height growth and survival, both of which are indicators of plant vigor. Analysis of clonal variation in NRS showed an intermediate level of significance ( P  = 0.083), and a significant clone by site interaction ( P  = 0.024). On coarse gravel outwash, the more vigorous clones for height growth also produced more RS, indicating the absence of a potential trade-off in carbohydrate resource allocation between height growth of the ortet (mother plant) and its capacity for colony formation and spread via RS. It appears that RS quickly become independent sources of carbohydrate production. However, there was no relationship between clonal height growth and NRS on the rock overburden. Loose sand and gravel outwash deposits promoted a more rapid spread of the shallow horizontal root network than the less penetrable shale rock overburden that dominates this former coal mine site. Highlights: Salix interior is one of the few willows that form multi-stemmed vegetative colonies arising from a horizontal root network. Clonal field tests on very low soil nitrogen sites showed significant genetic variation. Rate of colony formation and expansion via root stems depends on soil texture. Genotypes (clones) with the best height growth also produced more root stems. Colony-forming willows may provide a major cost advantage over conventional short-rotation, coppice-based woody biomass plantations.